Being an expert in pandemic times: negotiating epistemic authority in a media interaction - D'Angelo, Mariapia; Orletti, Franca (Frontiers in Communication, 2023)
Since the so-called phase one of the Coronavirus pandemic, media professionals have shown great attention to communication about the epidemic, so much so that a "glottology of Covid-19" has even been advocated to reflect on war metaphors referring to the disease. Despite media solicitations, however, reflection on communication at the time of Covid was not immediately the subject of linguistic analysis, at least in the Italian context. However, the issue of the relationship between language and culture, society, and thought has recently been explored in the face of the limitation of only formal analyses on language at the time of Covid. In the first stage, it quickly became apparent that the people in charge of institutional communication were used to talking mostly with experts on public health problems or research results, without the necessary training to modulate their language according to the degree of specialization of the audience. Instead, it is currently possible to detect an improvement in communication skills, and to observe the emergence of opposing factions with respect to the new resources of both preventive and therapeutic medicine, respectively the pro-vax and no-vax movements. Much of the debate around these conflicts has been dominated by the fear of the consequences of both the illness and the treatments, together with apprehension about the progressive restriction of individual freedoms. These issues have been the focus of many Italian TV talk shows, such as the program "Non è l’Arena." In the episode of 9/25/21, which is the subject of this article, the positions expressed in favor of one argument or the other would seem to adopt different mechanisms for managing the epistemic mode of certainty/uncertainty, such as semantic-syntactic and rhetorical-pragmatic devices, as well as conversational moves. This paper is aimed at describing the management of certainty/uncertainty in a media context through the qualitative fine-grained analysis of the interactional exchanges between host and representatives of different positions in the dual theoretical framework of classical rhetoric and conversational analysis, which although starting from entirely different scientific paths, share the vision of the centrality of speech in human action.